1982
DOI: 10.1017/s002237780000012x
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén soliton in a low-beta plasma

Abstract: An exact nonlinear Alfvén wave in a low-β plasma is investigated. Super Alfvén solitons with a density depression are found to exist. The analytical result for the small-amplitude soliton is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 6 publications
3
57
0
Order By: Relevance
“…Later, several other investigations on the nonlinear Alfvén waves [10]- [14] in e-i plasmas were carried out. For example, Seyler and Lysac [13] have extended the work of Hasegawa and Mima [9] and Shukla et al [11] by considering the nonlinear propagation of low-frequency (ω < ω ce , where ω ce is the electron cyclotron frequency) dispersive inertial and KAWs and by retaining the linear and nonlinear perpendicular ion inertial and ion Lorentz forces. They showed that the planar dispersive Alfvénic solitary structures cannot exist.…”
Section: Introductionmentioning
confidence: 99%
“…Later, several other investigations on the nonlinear Alfvén waves [10]- [14] in e-i plasmas were carried out. For example, Seyler and Lysac [13] have extended the work of Hasegawa and Mima [9] and Shukla et al [11] by considering the nonlinear propagation of low-frequency (ω < ω ce , where ω ce is the electron cyclotron frequency) dispersive inertial and KAWs and by retaining the linear and nonlinear perpendicular ion inertial and ion Lorentz forces. They showed that the planar dispersive Alfvénic solitary structures cannot exist.…”
Section: Introductionmentioning
confidence: 99%
“…Neglecting the terms proportional to Q, namely 3 and 4 , in Eq. (57), the Sagdeev potentials obtained by Hasegawa and Mima (1976) and Shukla et al (1982) can be recovered from Eq. (57) in the limits of α 1 and α 1, respectively.…”
Section: Sagdeev Equation For Skawmentioning
confidence: 99%
“…The correction effect of a finite β was considered by Yu and Shukla (1978). A similar case, but for β Q 1, was investigated by Shukla et al (1982). They also showed the existence of SKAWs, but accompanied by a dip density soliton.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a low-␤ (␤ӶQ) plasma magnetized by a uniform ambient magnetic field B 0 along the z direction, the electron motion equation parallel to B 0 , including the collisional resistance, can be written as follows: 11,12,16,18 Ϫ͑e…”
mentioning
confidence: 99%